2019
DOI: 10.1103/physrevlett.122.136801
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Resistive Switching: Multistate Functionality due to Electric-Field-Induced Healing of Dead Layers

Abstract: Materials exhibiting reversible resistive switching in electrical fields are highly demanded for functional elements in oxide electronics. In particular, multilevel switching effects allow for advanced applications like neuromorphic circuits. Here we report on a structurally driven switching mechanism involving the so-called "dead" layers of perovskite manganite surfaces. Forming a tunnel barrier whose thickness can be changed in monolayer steps by electrical fields, the switching effect exhibits well-defined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…From the fitting of the current-thickness dependence in Figure 10e by the Simmons model [35] reasonable values for the minimum barrier thickness z 0 ≈ 1.3 nm and the electrical contact area A ≈ 2.0 nm 2 were obtained. The evaluated barrier height φ = 46 meV has to be considered as a rough estimate, but in any case, φ cannot exceed 60 meV.…”
Section: Electric Field Effectmentioning
confidence: 76%
See 3 more Smart Citations
“…From the fitting of the current-thickness dependence in Figure 10e by the Simmons model [35] reasonable values for the minimum barrier thickness z 0 ≈ 1.3 nm and the electrical contact area A ≈ 2.0 nm 2 were obtained. The evaluated barrier height φ = 46 meV has to be considered as a rough estimate, but in any case, φ cannot exceed 60 meV.…”
Section: Electric Field Effectmentioning
confidence: 76%
“…Electric-field-driven resistive switching, being widely spread phenomenon in heterostructures of correlated oxides, including perovskite manganites, [89][90][91] was believed to be promising for novel multistate resistive memory (memristive) applications including advanced neuromorphic computing [73,92,93]. Recently [35] we have demonstrated that a multistate functionality can be obtained in an intrinsic heterostructure, comprising the "dead layer" (DL) at the surface of a manganite film. The DL acting as a tunneling barrier plays a most active role being electrically switchable in monolayer steps between two intrinsically well-defined resistance states.…”
Section: Electric Field Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Various materials have shown the RS effect, but transition metal oxides have attracted considerable attention because of their potential applications in nonvolatile memory . The RS phenomenon was observed in binary oxides such as Fe 2 O 3 , NiO, and ZnO and perovskite‐based oxides such as SrTiO 3 and manganites . Among various manganite materials, RS has been studied considerably in yttrium‐based manganites .…”
Section: Introductionmentioning
confidence: 99%